Impedance estimation of single-phase diode bridge rectifier using kalman filter - Nor Syuhaida, Othman (2022)
Today, the majority of electronic loads are non-linear. Electronic ballasts for discharge lamps, audio equipment, and personal computers are examples of non-linear loads. DC voltage is used to power these electronic loads. It is important to convert AC voltage to DC voltage since the power distribution system operates on AC voltage. In low-power applications, single phase rectifiers convert AC electricity to DC voltage. The aspects that influence nonlinear loads and allow a power quality study include power factor, displacement factor, and harmonic distortion. The study of these phenomena has grown in popularity as this type of load has become more prevalent in residential and commercial environments. Nonlinear load modeling is a critical tool for resolving this issue. Then specialized research into the modeling of these loads is required. As a result, this study create a Kalman filter model by using MATLAB Simulink for estimating the RLC parameters of a single-phase diode bridge rectifier. The system design was carried out using the MATLAB Simulink platform, with the appropriate RLC parameters taken from relevant literature studies. This study discovered that the amount of process noise in a system indicates the system's performance. The simulation is finished when all of the required conditions are met, which means the accuracy attained is at least 90%. When compared to the Analytical technique, simulation results show that the proposed method is more accurate. It specifies that with a modest value of process noise, the precision of equivalent capacitance, resistance, and inductance becomes more precise. For Section 1, the percentage of accuracy improved by 0.26%, 0.6%, and 9.84%, respectively, for resistance, inductance, and capacitance. Besides, for Section 2, the percentage of accuracy increased by 0.16%, 0.1%, and 1.3% for resistance, inductance, and capacitance respectively. Finally, the Kalman Filter can be used to calculate the R, L, and C parameter values for a single-phase diode bridge rectifier.